2008
DOI: 10.1021/bi800681g
|View full text |Cite
|
Sign up to set email alerts
|

The Regulatory β Subunit of Phosphorylase Kinase Interacts with Glyceraldehyde-3-phosphate Dehydrogenase

Abstract: Skeletal muscle phosphorylase kinase (PhK) is an (αβγδ) 4 hetero-oligomeric enzyme complex that phosphorylates and activates glycogen phosphorylase b (GPb) in a Ca 2+ -dependent reaction that couples muscle contraction with glycogen breakdown. GPb is PhK's only known in vivo substrate; however, given the great size and multiple subunits of the PhK complex, we screened muscle extracts for other potential targets. Extracts of P/J (control) and I/lnJ (PhK deficient) mice were incubated with [γ-32 P]ATP with or wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…GAPDH and GST were verified by reciprocal coIP in our study, whereas the effect of SOD was demonstrated previously with tempol, a SOD mimetic that interacts with BK␣ in CHO cells, causing an increase in peak current (54). GAPDH is involved in oxidative phosphorylation (55), and its activation is one of the primary effects of Ca 2ϩ influx into the mitochondrion (56 -58). Thus, GAPDH gene expression in the Organ of Corti increases during ischemic conditions (59), a likely result of Ca 2ϩ overload (60).…”
Section: Bk Protein Folding and Intracellular Ca 2ϩ Stores-ap-supporting
confidence: 75%
“…GAPDH and GST were verified by reciprocal coIP in our study, whereas the effect of SOD was demonstrated previously with tempol, a SOD mimetic that interacts with BK␣ in CHO cells, causing an increase in peak current (54). GAPDH is involved in oxidative phosphorylation (55), and its activation is one of the primary effects of Ca 2ϩ influx into the mitochondrion (56 -58). Thus, GAPDH gene expression in the Organ of Corti increases during ischemic conditions (59), a likely result of Ca 2ϩ overload (60).…”
Section: Bk Protein Folding and Intracellular Ca 2ϩ Stores-ap-supporting
confidence: 75%
“…57,58 More recently, GAPDH was shown to be a Ca 2+ -dependent substrate of phosphorylase kinase providing a direct link between glycogenolysis and glycolysis in skeletal muscle. 59 Ganon et al also identified 6 phospholabeled glycolytic enzymes (PKM2, ENO3, ALDOA, LDHA, PGM2, and TPI1) in rat skeletal muscle, and demonstrated an age-dependent change in the phospholabeling of the LDHA and ENO3. 38 Our findings are supported by recent phosphoproteomic studies of human cell lines that have documented serine/threonine phosphorylation of several glycolytic enzymes, and in many cases at the same sites as those identified in the present study.…”
Section: Discussionmentioning
confidence: 96%
“…Our data indicate that under basal conditions, serine/threonine phosphorylation is more frequent than tyrosine phosphorylation of glycolytic enzymes in human skeletal muscle. Only a few earlier studies of mammalian liver and muscle have provided some evidence for serine/threonine phosphorylation of glycolytic enzymes (PKM2, PFKM), and suggested a role for PKA and CaMK in the regulation of these enzymes. , More recently, GAPDH was shown to be a Ca 2+ -dependent substrate of phosphorylase kinase providing a direct link between glycogenolysis and glycolysis in skeletal muscle . Ganon et al also identified 6 phospholabeled glycolytic enzymes (PKM2, ENO3, ALDOA, LDHA, PGM2, and TPI1) in rat skeletal muscle, and demonstrated an age-dependent change in the phospholabeling of the LDHA and ENO3 .…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatic analysis of potential phosphorylation motifs within the GAPDH primary amino acid sequence did, however, indicate a phosphorylation motif that matched the insulin receptor kinase conserved motifs, possibly substantiating some link between GAPDH regulation by tyrosine phosphorylation and fuel metabolism ( Appendix S2 ; Obenauer, Cantley & Yaffe, 2003 ). Additionally, GAPDH serine/threonine phosphorylation has also been well established as an important regulatory mechanism ( Kawamoto & Caswell, 1986 ; Reiss et al, 1996 ; Choudhary, De & Banerjee, 2000 ; Tisdale, 2002 ; Singh et al, 2004 ; Tisdale & Artalejo , 2007 ; Boulatnikov et al, 2008 ; Baba et al, 2010 ; Huang et al, 2011 ). Bioinformatic assessment of the potential serine/threonine phosphorylation sites suggest PKC and CaMK as likely modifiers of GAPDH ( Appendix S2 ), which coincides with the results observed in this study ( Fig.…”
Section: Discussionmentioning
confidence: 99%